Transcriptomic signatures across a critical sedimentation threshold in a major reef-building coral - Lock, Colin; Gabriel, Melissa M.; Bentlage, Bastian (Frontiers in Physiology, 2024)
Sedimentation is a major cause of global near-shore coral reef decline. Although the negative impacts of sedimentation on coral reef community composition have been well-documented, the effects of sedimentation on coral metabolism in situ have received comparatively little attention. Using transcriptomics, we identified gene expression patterns changing across a previously defined sedimentation threshold that was deemed critical due to changes in coral cover and community composition. We identified genes, pathways, and molecular processes associated with this transition that may allow corals, such as Porites lobata, to tolerate chronic, severe sedimentation and persist in turbid environments. Alternative energy generation pathways may help P. lobata maintain a persistent stress response to survive when the availability of light and oxygen is diminished. We found evidence for the expression of genes linked to increased environmental sensing and cellular communication that likely allow P. lobata to efficiently respond to sedimentation stress and associated pathogen challenges. Cell damage increases under stress; consequently, we found apoptosis pathways over-represented under severe sedimentation, a likely consequence of damaged cell removal to maintain colony integrity. The results presented here provide a framework for the response of P. lobata to sedimentation stress under field conditions. Testing this framework and its related hypotheses using multi-omics approaches can deepen our understanding of the metabolic plasticity and acclimation potential of corals to sedimentation and their resilience in turbid reef systems.